The Importance of Students' Scholarship (Scientific) Ethics at Universtias Islam Negeri (UIN) Mataram College in the Islamic Intellectual Tradition - Septiana Ade Karunia; Fathurrahman Muhtar; Maimun Zubair (CV. Creative Tugu Pena, 2024)
The purpose of this study is motivated by the importance of student academic ethics to the campus environment and to explain the impact of the principles of academic ethics in the Islamic intellectual tradition. Good ethics and bad ethics become the main focus in understanding and shaping student behavior. As the basis of character building, good ethics guides students in living an academic life with integrity and responsibility. On the other hand, understanding bad ethics creates awareness of actions that can harm integrity and trust in the academic world. This type of research uses a qualitative approach, using field study research (Field Research), the data collection technique uses interviews, observation and documentation. The results show that in the Islamic intellectual tradition, strong ethical principles have a very important role in shaping honest, skillful, and responsible individuals. In the context of education, the ethics of literacy in the Islamic intellectual tradition helps foster an attitude of discipline, honesty, and hard work in students. It can help to build a positive image of educational institutions and society, which is expected to improve the quality of education in the campus environment.